Kaizen costing : extending NPD process to suppliers - Santos, António Carlos Pereira dos (2009)
Kaizen Costing (KC) involves several procedures that allow costs to be reduced through continuous improvements during the production phase of the product life cycle. Internal and external collaborators, i.e. employees and suppliers are involved in this process. KC expands the cost management philosophy of Target Costing (TC) to the manufacturing process. TC is a cost management approach applied in new product development processes [1]. KC is used later and it permits to involve suppliers definitely into the global cost management effort for they have the manufacturing process knowledge. Based on a case study and drawing upon empirical evidence relating to the adoption and use of kaizen costing practices in a supplier belonging to a global supply chain in the automotive industry, this work offers empirical evidence on the role of kaizen costing related procedures to the competitiveness of suppliers in the automotive industry. The use of kaizen costing practices by this supplier is formally and informally pushed by its clients in order to be recognized and admitted as a supplier, i.e. for legitimacy purposes of the supplier. However, the results of this research demonstrate that strategic issues may play also a relevant role in explaining the use of Kaizen costing practices.